Magnetic refrigeration: analysis located electron model - John Jairo Hoyos Quintero; Juan Esteban Velásquez; Farid Chejne Janna; Alan Francis Hill Betancourt (Revista Facultad de Ingeniería Universidad de Antioquia, 2005)
Magnetic refrigeration is a technology with great commercial potential. Energy consumption and environmental impact associated with this technology are lower than those from conventional refrigeration systems. This paper presents the main aspects of the theory of the magnetocaloric effect. In addition, the application of the located electron model to magnetic refrigeration is analyzed. The model permits just a qualitative description of the behaviour of magnetocaloric effect in the vicinity of the magnetic transformation temperature.